Energy And Physics - Time-Life Books (Time-Life Books : Hong Kong, 1994)
This volume offers an accessible and visual introduction to fundamental physics and energy concepts geared toward young readers and general science enthusiasts. Key sections include: Types and sources of energy (chemical, thermal, kinetic, potential) Forces and motion (Newton$1 (Bs laws, friction) Electricity and magnetism basics Light, heat, sound, and thermodynamics Emerging physics topics and real-world applications Content is presented in a clear Q&A-style format with vibrant photographs, diagrams, and explanatory captions to enhance understanding.s
Keywords: Physics